Optimising treatment strategies in spinal ependymoma based on 20 years of experience at a single centre. (July 2016) - Keil, Vera C.; Schmitt, Anne J.; Martin, Sean C.; Cadoux-Hudson, Tom A.D.; Pereira, Erlick A.C.
Highlights: Spinal ependymomas should be radically resected whenever possible. Radiotherapy showed no beneficial effect after subtotal resection. Follow up imaging should take place over at least five years. There is an aggressive course in cases of recurrent tumour. Abstract: Spinal ependymomas are rare tumours, with total resection favoured where possible. Several case series assessing the outcome following neurosurgical treatment for spinal ependymoma advocate the usage of adjuvant radiotherapy in cases of subtotal resection, or in unencapsulated tumours. We assessed the outcome of 61 consecutive cases of spinal ependymoma in a single centre over a 20 year period using a variety of outcome measures. Sex distribution was equal, with a mean age at surgery of 43.6 years (range 5–76 years). Overall, most tumours occurred in the lumbosacral region (70.5%), with fewer in the thoracic (27.9%) and cervical regions (18.0%). Myxopapillary features were seen in 41.0% of tumours, and were more common when occurring in the lumbar region (51.2%). Gross total resection was achieved in 52.5%, subtotal resection in 37.7% and biopsy alone in 9.8% of patients and 31.1% received adjuvant radiotherapy. Two-thirds of patients achieved an excellent post-operative neurological outcome (Frankel grade E). Tumour recurrence was rare. Gross total resection and good preoperative neurological condition were most strongly predictive of good outcome. Post-operative radiotherapy did not seem to confer survival benefit in this case series, even in cases of incomplete resection, leading us to question its utility for all cases of spinal cord ependymoma.